Avaliação da intervenção socioeducativa sobre a violência na escola - Campos, J.; Sebastião, João; Merlini, S.; Chambino, M. (ATAS do VI Encontro do CIED – I Encontro Internacional em Estudos Educacionais. Avaliação: Desafios e Riscos, 2014)
The research developed through the project Estratégias de Intervenção socioeducativa em contextos sociais complexos concerns the assessment of social and educational policies, particularly in what regards safety in school contexts marked by social and cultural complexity and diversity. The assessment focused on the analysis of the social and educational intervention strategies of three schools of the Lisbon Metropolitan Area on the problem of school violence. Assuming that school violence is a multidetermined and multifaceted phenomenon the research engaged an approach that includes the intervention/action of formal institutions and of social agents as mechanisms that structure and regulate conceptions and practices of school violence. The gathering and systematization of information was centered on the intervention strategies developed locally by the schools, on one hand, and the perspectives of the different stakeholders, on the other hand, considering students, teachers, school directors and representatives from the local organizations and institutions. The methodology intersected extensive and intensive methods, combining techniques such as Observation, Interviews, Focus Groups, Questionnaires, Social Network Analysis and Document Analysis. At the final stage, the various actors were involved on the discussion and analysis of the results, as well as the validation of an intervention strategy to deal with school violence. This strategy was the main result of the projectand resulted from a dynamic assessment and participative procedures. The presentation at the VI CIED Conference focused on the procedures and key outputs of this research project.